Analysis of Little Millets by High-resolution Mass Spectroscopy Focusing the Components of Little Millets Effective in the Management of Diabetes Mellitus - Reddy, Prof. K. Ramachandra (Asian Journal of Pharmaceutics (AJP), 2023)
Diabetes mellitus, a metabolic disorder, poses significant health risks. For diabetics, weight loss, exercise, oral glucose-lowering medicines, effective diet can help them to achieve adequate glycemic control. Millets contain many types of antioxidant elements such as phenolic flavonoids, which are important in controlling glucose levels in the body. Taking the millet diet physiologically helps to control the gluconeogenesis process. Little Millet is possessing rich antioxidant properties which helps to prevent metabolic and lifestyle disorders such as obesity, diabetes, and retinopathy. Through UHPLC-Q-TOF-MS/MS system, major antidiabetic compounds are revealed such as hispidin, caffeine, aicar, ketotifen, maltitol, tacrolimus, and pipemidic acid. These compounds indirectly control body metabolism to cope-up with diabetes mellitus